Integration of ESD-based EDP model to improve students' ability to apply physics concepts to sustainable energy - Pratama, Andhika Aditiya; Nuryadin, Atin; Efwinda, Shelly; Subagiyo, Lambang (Education and Development Research, 2026)
This study aims to determine the effect of the Engineering Design Process (EDP) learning model based on Education for Sustainable Development (ESD) in improving students' ability to apply physics concepts to sustainable energy, particularly in the topics of energy transformation and renewable energy at the senior high school level. This research used a pre-experimental method with a one-group pretest-posttest design. The research subjects were 33 students of class X at senior high school 1 Muara Bengkal, Indonesia. The instrument used was an essay test based on the context of sustainable energy to measure the ability of students before and after learning. The results showed an increase in the ability of students, with an average pre-test score of 20.61 to 81.67 in the post-test. The N-Gain value obtained was 0.76, including in the high category. In addition, the results of non-parametric statistical tests using the Wilcoxon Signed Rank Test showed a significant difference between the pre-test and post-test scores (p < 0.05), which indicated that the ESD-based EDP model had a significant effect on improving students' abilities. The one-group pretest-posttest design without a control group limits the generalizability of the findings and the extent to which learning gains can be attributed solely to the implemented model. This model encourages learners not only to understand physics concepts but also to relate these concepts to real contexts and design creative solutions that support the Sustainable Development Goals (SDGs). The learning approach also promotes responsible decision-making and environmental awareness, which are essential components of sustainable development education. Therefore, the ESD-based EDP model is effectively applied in physics learning to improve the ability to apply physics concepts to sustainable energy.